1998
DOI: 10.1097/00000372-199810000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Subungual Myxoid Pleomorphic Fibroma

Abstract: The authors report an example of pleomorphic fibroma in a unique site: the subungual space of the thumb. A 54-year-old man presented with paronychia and markedly thickened hyperkeratotic nail. The nail plate was removed, and an exophytic, red, friable, granulation tissue-like lesion was revealed subungually. The lesion was diagnosed clinically as pyogenic granuloma. Excisional biopsy was performed. Histologically, the lesion showed a hypocellular fibroma with myxoid areas and dilated blood vessels. Intersperse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 14 publications
4
26
0
Order By: Relevance
“…One phenotypic alteration that is not widely acknowledged, but possible is fibroblast multinucleation [68]. Additionally, several other multinucleated giant cells including foreign body giant cells (FBGCs), Langhans’ cells, and osteoclasts, all commonly derived from a macrophage cell origin are known [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One phenotypic alteration that is not widely acknowledged, but possible is fibroblast multinucleation [68]. Additionally, several other multinucleated giant cells including foreign body giant cells (FBGCs), Langhans’ cells, and osteoclasts, all commonly derived from a macrophage cell origin are known [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified multinucleated cells in vivo ostensibly of fibroblast origin [6, 7], one describing cells appearing as “bizarre, atypical fibroblasts with hyperchromatic and large, pleomorphic nuclei and multinucleated floret-like giant cells”[8]. Several studies describe the presence of multinucleated fibroblasts in vitro [1821] and in vivo in pathologies such as fibrosis and cancer and in aged tissue [1–8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These balloon cells (not to be confused with multinucleated melanocytes) have been suggested to be of either neuronal or glial origin [159]. Floret giant cells have been observed in various neoplasms including multinucleate cell angiohistiocytoma, pleomorphic lipoma, giant cell fibroblastoma, giant cell collagenoma [160], neurofibroma [161], pleomorphic fibroma [162], and dermatofibroma [163]. The name "floret" reflects the unique nuclear arrangement around the periphery of the cell, similar to petals on a flower.…”
Section: Multinucleated Giant Cellsmentioning
confidence: 99%
“…32 To date, 2 cases of subungual pleomorphic fibromas have been reported. 32,33 Hsieh et al 32 reported a 66-year-old woman who presented with a 40-year history of a nail deformity of …”
Section: Pleomorphic Fibromamentioning
confidence: 99%